2016
DOI: 10.1007/s13193-016-0604-3
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception: a Rare Complication After Feeding Jejunostomy; a Case Report

Abstract: Feeding jejunostomy (FJ) is a commonly done surgical procedure for enteral nutrition. Intussusception is one of the rare complications of FJ. Clinical presentation may be similar to other causes of small bowel obstruction. Intussusception should be suspected if a patient with jejunostomy tube develops upper gastrointestinal obstructive symptoms, which are relieved by nasogastric tube drainage. CT or ultrasonography (USG) can help to confirm the diagnosis. It can be relieved spontaneously or sometimes requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Minor complications - leakage, dislocation, superficial infection, tube occlusion - make up the vast majority of occurrences[9]. Severe complications are exceedingly rare but can be life-threatening, including small bowel necrosis, intestinal torsion, and intussusception[42-44]. Patients who suffer more serious complications related to their jejunostomy tubes often are unable to tolerate enteral feeding; nearly 20% of patients with feeding tubes still required some period of TPN administration, with 7% directly attributable to tube feeding intolerance or complications[45].…”
Section: Methods Of Artificial Feeding After Esophagectomymentioning
confidence: 99%
“…Minor complications - leakage, dislocation, superficial infection, tube occlusion - make up the vast majority of occurrences[9]. Severe complications are exceedingly rare but can be life-threatening, including small bowel necrosis, intestinal torsion, and intussusception[42-44]. Patients who suffer more serious complications related to their jejunostomy tubes often are unable to tolerate enteral feeding; nearly 20% of patients with feeding tubes still required some period of TPN administration, with 7% directly attributable to tube feeding intolerance or complications[45].…”
Section: Methods Of Artificial Feeding After Esophagectomymentioning
confidence: 99%
“…Additionally, feeding through sites distal to the pylorus is associated with decreased risks of certain complications such as aspiration and dehydration. 23 Although we found that inpatient resource utilization is not higher in patients with j-tubes, it is possible that patients with j-tubes may utilize outpatient resources and emergency department (ED) care more frequently. Kidane et al found that feeding tube-related problems were the most common cause (39%) of returning to the ED within the first year after esophagectomy.…”
Section: Discussionmentioning
confidence: 72%
“…Its diagnosis is difficult as initially it does not interfere with feeding habits of patient and with advanced disease, there are signs and symptoms of obstruction, i.e. vomiting, pain abdomen and inability to pass faeces and flatus [ 9 ]. The exact mechanism for occurrence of JTI is unknown; however, many mechanisms have been proposed - tip of the tube acting as a lead point, tube-induced inflammatory reaction causing hypertrophy of the mucosa which can form the lead point, retrograde peristalsis of jejunum due to vomiting and injecting force during feeding and reduced mesenteric fat in poorly built patients which allows free movement of intestine [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…vomiting, pain abdomen and inability to pass faeces and flatus [ 9 ]. The exact mechanism for occurrence of JTI is unknown; however, many mechanisms have been proposed - tip of the tube acting as a lead point, tube-induced inflammatory reaction causing hypertrophy of the mucosa which can form the lead point, retrograde peristalsis of jejunum due to vomiting and injecting force during feeding and reduced mesenteric fat in poorly built patients which allows free movement of intestine [ 9 ]. Our patient was of thin built secondary to decreased intake due to previous corrosive acid intake so there was minimal fat in the abdominal cavity, allowing free movement of bowel loops.…”
Section: Discussionmentioning
confidence: 99%